Comparison of the sealing ability of bioceramic sealer against epoxy resin based sealer: A systematic review & meta-analysis - Ramakumar Rekha; R. Kavitha; Ramanarayanan Venkitachalam; Singh VP. Prabath; S. Deepthy; Venugopal Krishnan (Journal of Oral Biology and Craniofacial Research)
Objective: This systematic review and meta-analysis aimed to evaluate if bioceramic sealers had superior sealing properties to epoxy resin-based sealers. Methodology: A systematic search was performed in the following databases: MEDLINE Ovid (from 1946 onwards), Scopus, Google Scholar, EBSCO, and a hand search of references of included articles was also done. In vitro and ex vivo studies were included. Risk of bias was assessed, and quantitative synthesis was performed for microleakage measured using vertical dye penetration, horizontal dye penetration, and dentin-sealer gap. Summary effect was reported as Standardized Mean Difference with 95% CI. Subgroup analysis was performed based on the imaging modalities, the obturation techniques, and the file systems employed. Results: A total of 24 studies were included. Meta-analysis demonstrated no significant difference between the sealing ability of bioceramic sealer and epoxy resin-based sealer when measured using the microleakage tests [SMD -0.59(95%CI: 1.74,0.55)]. Subgroup analysis revealed no significant differences except when manual K-files were used. Heterogeneity was low when sub-group analysis was done. Conclusion: Bioceramic sealers and epoxy resin-based sealers both exhibited comparable sealing ability.